Probing the interaction of the ipsilateral posterior parietal cortex with the premotor cortex using a novel transcranial magnetic stimulation technique. Issue 2 (February 2016) - Shields, Jessica; Park, Jung E.; Srivanitchapoom, Prachaya; Paine, Rainer; Thirugnanasambandam, Nivethida; Kukke, Sahana N.; Hallett, Mark
Highlights: A three-pulse, three site, transcranial magnetic stimulation technique can be used for examining a cortical network in human subjects. Preconditioning the posterior parietal cortex reverses the motor cortex inhibition produced by stimulation of premotor cortex. These experiments reveal a disynaptic connection from parietal to motor cortex via the premotor cortex. Abstract: Objective: Functional imaging studies have shown that control of planned movement involves a distributed network that involves the premotor (PMv) and posterior parietal cortices (PPC). Similarly, anatomical studies show that these regions are densely interconnected via white matter tracts. We therefore hypothesized that the PPC influence over the motor cortex is partly via a connection with the PMv. Methods: Using a novel three-pulse ipsilateral transcranial magnetic stimulation technique, we preconditioned the PPC (80% RMT) at ISIs from 4–15 ms prior to stimulating the PMv and M1 at ISIs of 4 and 6 ms. Results: As previously shown, PMv–M1 paired-pulse stimulation resulted in inhibition of the MEP (90% RMT, 4–6 ms) and PPC–M1 paired-pulse stimulation resulted in facilitation of the MEP (90% RMT, 4–8 ms). PPC–M1 paired-pulse stimulation at 80% RMT preconditioning had no effect on M1. PPC–PMv–M1 stimulation resulted in reversal of inhibition observed with PMv–M1 stimulation at ISIs ranging from 6 to 15 ms. Conclusions: The reversal of inhibition observed with PPC–PMv–M1 stimulation suggests that the parietal connection to the PMv plays a role in the modulation of M1. Significance: This is the first study to stimulate three intrahemispheric regions in order to test a disynaptic connection with M1. The described network may be important in a variety of movement disorders.